Career Choice, Marriage-Timing, and the Attraction of Unequals - Sylvain Dessy; Habiba Djebbari (Institute for the Study of Labor (IZA), 2005)
Both men and women wish to have a family and a rewarding career. In this paper, we show that the under-representation of women in high-powered professions may reflect a coordination failure in young women?s marriage-timing decisions. Since investing in a highpowered career imposes time strain, it precludes early participation in the marriage market. Delayed participation in the marriage market has a higher cost for women than for men because women have shorter fecundity horizons. Marriage prospects of high-powered women depend on the marriage-timing decisions of younger women. Under these assumptions, we show that women?s marriage-timing decisions exhibit strategic complementarities. Coordination failures in women?s marriage-timing decisions lead to persisting gender differences in career choices. Yet, differential fecundity is only necessary, but not sufficient to obtain gender inequality in high-powered professions. We discuss social changes that solve the coordination failure while achieving a Pareto-improvement in the society at large.
Keywords: J24; J16; J12; 330; marriage-timing; high-powered career; supermodular game; strategic complementarities; multiple equilibria; coordination failure